Tin-phosphorus composite material, tin-phosphorus-carbon composite material, preparation method of tin-phosphorus-carbon composite material, pole piece and electrochemical device
By depositing red phosphorus particles in porous tin-containing substances and heat treatment and carbon coating, tin phosphorus composite materials and tin phosphorus carbon composite materials are prepared, which solves the problems of volume expansion and poor conductivity of the phosphorus carbon material, and significantly improves the cycling performance and capacity performance of the battery.
Patent Information
- Application Number
- CN202411897967.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
AI Technical Summary
The existing phosphorus carbon materials have poor circulation and capacity performance in batteries due to their large volume expansion and poor conductivity.
Using tin-phosphorus composite materials and tin-phosphorus carbon composite materials, the material with lower volume expansion and better conductivity is formed by depositing red phosphorus particles in porous tin-containing substances and preparing through steps such as heat treatment and carbon coating.
The cycling performance and capacity performance of tin-phosphorus composite materials and tin-phosphorus carbon composite materials in batteries have been significantly improved, ensuring the efficient application of materials.
Smart Images

Figure CN119695119A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a tin-phosphorus composite material, a tin-phosphorus-carbon composite material, a preparation method thereof, a pole piece and an electrochemical device. Background Art
[0002] With the rapid development of the market, the market demand for portable electronic products and hybrid vehicles is also growing rapidly, which has promoted the research of power energy storage systems. Lithium-ion batteries have attracted widespread attention due to their high energy density and long cycle life. Among them, new phosphorus materials have attracted much attention due to their high theoretical capacity of about 2600mAh / g and suitable electronic potential. Their theoretical capacity is about 6-7 times that of graphite. However, due to their large volume expansion (over 300%) during charging and discharging, poor conductivity, poor life and capacity utilization, their application is limited. Therefore, researchers have also done a lot of work on the commercial application of this material: it has been confirmed that the electrochemical performance can be improved by designing and constructing new microstructure / nanophosphorus-based materials, including the introduction of conductive additives to improve electronic conductivity and adapt to volume change cycles, the preparation of nano / amorphous phosphorus to reduce the pressure of volume change and shorten the lithium ion diffusion path, and the formation of carbon-phosphorus bonds to stabilize phosphorus cycles.
[0003] Chinese patent application CN 116759556 A introduces a method for preparing a phosphorus-carbon composite negative electrode material, which includes first mixing phosphorus and carbon materials, and then pre-activating the mixture to obtain a pre-activated mixture; mixing and crushing the pre-activated mixture with water and a dispersant to obtain a primary slurry, and then mixing and grinding the primary slurry with a dispersing solvent to obtain a secondary slurry, and finally drying the secondary slurry to obtain a phosphorus-carbon composite negative electrode material. However, the cycle performance of the material still needs to be improved, and the material has not yet exerted the capacity advantage of phosphorus materials.
[0004] Therefore, it is urgent to propose a method to improve the capacity performance and cycle performance of phosphorus materials, comprehensively enhance the performance of phosphorus materials, and show excellent performance in both capacity performance and cycle performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects of the prior art that the phosphorus-carbon materials have large volume expansion and poor electrical conductivity, which leads to poor cycle performance and capacity performance of the battery assembled therefrom, and provide a tin-phosphorus composite material, a tin-phosphorus-carbon composite material and its preparation method, a pole piece and an electrochemical device. The tin-phosphorus composite material of the present invention has lower volume expansion and better electrical conductivity, and the battery assembled therefrom has better cycle performance and capacity performance. The tin-phosphorus-carbon composite material of the present invention has better electrical conductivity and lower charge transfer internal resistance. The battery assembled from the tin-phosphorus-carbon composite material has better electrochemical performance, especially better cycle performance and capacity performance. The preparation method of the tin-phosphorus composite material and the tin-phosphorus-carbon composite material of the present invention is simple, highly practical and can be operated on a large scale.
[0006] The present invention solves the above technical problems through the following solutions.
[0007] The invention provides a tin-phosphorus composite material, which comprises a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance.
[0008] In the present invention, the porous tin-containing material may be a conventional porous tin-containing material in the art, preferably including one or more of porous tin oxide, porous stannous oxide and porous tin, such as porous tin oxide.
[0009] In the present invention, the D50 of the red phosphorus particles may be 20-100 μm, preferably 40-80 μm, such as 50, 60 or 70 μm.
[0010] In the present invention, in the tin-phosphorus composite material, the mass ratio of phosphorus to tin may be (1-2):1, preferably (1.2-1.8):1, for example, 1.65:1, 1.59:1, 1.57:1, 1.56:1, 1.55:1, 1.52:1, 1.51:1, 1.50:1, 1.49:1, 1.46:1 or 1.44:1.
[0011] The present invention also provides a method for preparing a tin-phosphorus composite material, which comprises the following steps: heat treating and cooling a mixture comprising red phosphorus and a porous tin-containing substance to obtain a phosphorus-tin composite material; the heat treatment temperature is 400-500°C.
[0012] In the present invention, the mass ratio of the red phosphorus to the porous tin-containing material may be (6-8):(2-4), preferably (6-8):(2.5-3.5), for example 6:3 or 8:3.
[0013] In the present invention, the porous tin-containing material may be a conventional porous tin-containing material in the art, preferably including one or more of porous tin oxide, porous stannous oxide and porous tin, such as porous tin oxide.
[0014] The porous tin oxide can be prepared by conventional methods in the art, preferably by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12.
[0015] The inorganic tin source may be of conventional type in the art, and is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride or stannous chloride.
[0016] In the aqueous solution of the inorganic tin source, the molar volume ratio of the inorganic tin source to water may be (73-84) mmol:135 mL, for example 80 mmol:135 mL.
[0017] The type of the alkali is preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium bicarbonate and sodium carbonate, such as sodium hydroxide. The alkali is generally added in the form of an alkaline solution. The molar concentration of the alkaline solution is preferably 1-3 mol / L, such as 2 mol / L.
[0018] The molar ratio of the inorganic tin source to the base is preferably 1:(1.0-2.0), more preferably 1:(1.5-1.8), for example 1:1.6875.
[0019] The reaction is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The reaction temperature may be 50-90° C., such as 60-80° C. The reaction time may be 40-60 min, such as 50 or 55 min.
[0020] After the reaction, the steps of washing and drying conventional in the art are preferably further included. The washing preferably includes water washing and / or alcohol washing. The drying temperature may be 80-100°C, for example 90°C.
[0021] In the present invention, the temperature of the heat treatment is preferably 420-480°C, such as 450°C.
[0022] In the present invention, the rate of heating from room temperature to the temperature of the heat treatment may be 5-10° C. / min, such as 6, 7, 8 or 9° C. / min.
[0023] In the present invention, the heat treatment time may be 2-4 hours, for example 3 hours.
[0024] In the present invention, the initial pressure of the system during the heat treatment may be 0.5-1.5 MPa, for example 1 MPa. The initial pressure may be obtained by charging an inert gas.
[0025] In the present invention, the terminal temperature of the cooling may be 260-300°C, such as 260, 270, 280 or 290°C.
[0026] In the present invention, the cooling rate from the heat treatment temperature to the cooling end point temperature may be 1-3° C. / min, for example 2° C. / min.
[0027] In the present invention, after cooling to the end temperature, the cooling time may be continued for 16-28 hours, such as 22 or 26 hours.
[0028] In the present invention, after cooling, preferably a washing and purification step is further included, preferably by washing and purification with carbon disulfide.
[0029] The present invention also provides a tin-phosphorus composite material, which is prepared by the above-mentioned preparation method.
[0030] The present invention also provides a tin-phosphorus-carbon composite material, which includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-phosphorus-carbon composite particles, and second gaps are distributed between the tin-phosphorus-carbon composite particles;
[0031] Among them, a single tin-phosphorus-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, and a first gap is distributed between the shell layer and the inner core; wherein the inner core includes a tin-phosphorus composite material, and the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance; the shell layer includes a carbon layer.
[0032] In the present invention, the several means at least 2.
[0033] In the present invention, the D50 of the tin-phosphorus-carbon composite material may be 300-460 nm, preferably 330-430 nm, such as 410, 400, 380, 370, 360 or 350 nm.
[0034] In the present invention, the phosphorus content of the tin-phosphorus-carbon composite material may be 32%-45%, preferably 35%-42%, for example 39.9%, 39.4%, 39.2%, 38.9%, 38.7%, 38.5%, 38.4%, 38.1%, 37.8%, 37.6% or 37.5%.
[0035] In the present invention, the tin content of the tin-phosphorus-carbon composite material may be 19%-31%, preferably 22%-28%, for example 26.3%, 26.1%, 25.9%, 25.7%, 25.6%, 25.3%, 25.1%, 24.9%, 24.8% or 24.2%.
[0036] In the present invention, the carbon content of the tin-phosphorus-carbon composite material may be 20%-33%, preferably 23%-30%, for example 28.3%, 27.9%, 27.6%, 27.3%, 27.2%, 27.1%, 26.9%, 26.8% or 25.6%.
[0037] In the present invention, the oxygen content of the tin-phosphorus-carbon composite material may be 2%-13%, preferably 5%-10%, for example 7.89%, 7.83%, 7.77%, 7.71%, 7.68%, 7.59%, 7.53%, 7.47%, 7.44% or 7.26%.
[0038] The content of each element mentioned above represents the percentage of the mass of each element to the mass of the tin-phosphorus-carbon composite material.
[0039] In the present invention, in the single tin-phosphorus-carbon composite material, the carbon layer further includes heteroatoms.
[0040] The heteroatom may be one or more of nitrogen, phosphorus, sulfur and boron, such as nitrogen.
[0041] Wherein, the content of the heteroatom may be 0.1-0.65%, preferably 0.2%-0.55%, such as 0.87%, 0.83%, 0.82%, 0.77%, 0.76%, 0.75%, 0.74%, 0.72%, 0.71%, 0.69%, 0.68% or 0.59%. The content of heteroatom indicates the percentage of the mass of heteroatom to the mass of tin-phosphorus-carbon composite material.
[0042] The present invention also provides a method for preparing a tin-phosphorus-carbon composite material, which comprises the following steps:
[0043] S1, heat-treating and cooling a mixture including red phosphorus and a porous tin-containing substance to obtain a tin-phosphorus composite material; the heat-treating temperature is 400-500° C.;
[0044] S2, coating the tin-phosphorus composite material with silicon dioxide to form a silicon dioxide layer to obtain a first precursor; mixing the aqueous dispersion of the first precursor and an oil phase solution containing an emulsifier, removing the solvent and performing heat treatment to obtain a second precursor;
[0045] S3, carbon-coating the second precursor, removing the silicon dioxide layer, and obtaining a third precursor;
[0046] S4, coating the third precursor with graphene to obtain a tin-phosphorus-carbon composite material.
[0047] In S1 of the present invention, the mass ratio of the red phosphorus to the porous tin-containing material may be (6-8):(2-4), preferably (6-8):(2.5-3.5), for example 6:3 or 8:3.
[0048] In S1 of the present invention, the porous tin-containing material may be a conventional porous tin-containing material in the art, preferably including one or more of porous tin oxide, porous stannous oxide and porous tin, such as porous tin oxide.
[0049] The porous tin oxide can be prepared by conventional methods in the art, preferably by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12.
[0050] The inorganic tin source may be of conventional type in the art, and is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride or stannous chloride.
[0051] In the aqueous solution of the inorganic tin source, the molar volume ratio of the inorganic tin source to water may be (73-84) mmol:135 mL, for example 80 mmol:135 mL.
[0052] The type of the alkali is preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium bicarbonate and sodium carbonate, such as sodium hydroxide. The alkali is generally added in the form of an alkaline solution. The molar concentration of the alkaline solution is preferably 1-3 mol / L, such as 2 mol / L.
[0053] The molar ratio of the inorganic tin source to the base is preferably 1:(1.0-2.0), more preferably 1:(1.5-1.8), for example 1:1.6875.
[0054] The reaction is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The reaction temperature may be 50-90° C., such as 60-80° C. The reaction time may be 40-60 min, such as 50 or 55 min.
[0055] After the reaction, the steps of washing and drying conventional in the art are preferably further included. The washing preferably includes water washing and / or alcohol washing. The drying temperature may be 80-100°C, for example 90°C.
[0056] In S1 of the present invention, the temperature of the heat treatment is preferably 420-480°C, for example 450°C.
[0057] In S1 of the present invention, the rate of heating from room temperature to the temperature of the heat treatment may be 5-10° C. / min, such as 6, 7, 8 or 9° C. / min.
[0058] In S1 of the present invention, the heat treatment time may be 2-4 hours, for example 3 hours.
[0059] In S1 of the present invention, the initial pressure of the system during the heat treatment may be 0.5-1.5 MPa, for example 1 MPa. The initial pressure may be obtained by charging an inert gas.
[0060] In S1 of the present invention, the terminal temperature of the cooling may be 260-300°C, such as 260, 270, 280 or 290°C.
[0061] In S1 of the present invention, the cooling rate from the temperature of the heat treatment to the cooling end point temperature may be 1-3°C / min, for example 2°C / min.
[0062] In S1 of the present invention, after cooling to the end temperature, the cooling time may be continued for 16-28 hours, such as 22 or 26 hours.
[0063] In S1 of the present invention, after cooling, preferably a washing and purification step is also included, preferably by washing and purification with carbon disulfide.
[0064] In S1 of the present invention, the structure of the tin-phosphorus composite material may include a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance.
[0065] In S2 of the present invention, the method for preparing the tin-phosphorus composite material by coating it with silicon dioxide preferably comprises the following steps: mixing the tin-phosphorus composite material, a silicon source and an ammonia solution, acid washing and heat treatment.
[0066] The type of silicon source can be conventional in the art, preferably silicate or silicate. The silicate is preferably ethyl orthosilicate and / or methyl orthosilicate. The silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate.
[0067] The mass percentage of ammonia in the ammonia solution is preferably 25%-30%, for example 28%.
[0068] The mass volume ratio of the tin-phosphorus composite material to the silicon source is preferably (2-5) g: (3-10) mL, for example 4 g: 7 mL or 3.5 g: 7 mL.
[0069] The mass ratio of the tin-phosphorus composite material to the volume ratio of the ammonia is preferably (6-10) g:70 mL, such as 4 g:70 mL or 3.5 g:70 mL.
[0070] The mixing time is preferably 50-60 min, such as 55 min.
[0071] The acid used for pickling can be a conventional inorganic acid in the art, such as hydrochloric acid. The pickling generally uses an aqueous solution of an acid, such as an aqueous solution of an acid with a molar concentration of 2M.
[0072] After the acid washing and before the heat treatment, it is preferred to further include conventional steps of filtration, washing and drying in the art.
[0073] The temperature of the heat treatment is preferably 300-400° C., such as 350° C. The time of the heat treatment is preferably 15-30 h, such as 24 h. The rate of heating from room temperature to the temperature of the heat treatment is preferably 1-10° C. / min, such as 3° C. / min.
[0074] In S2 of the present invention, the structure of the first precursor may include a tin-phosphorus composite material and a silicon dioxide layer coating the tin-phosphorus composite material, and the structure of the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance.
[0075] In S2 of the present invention, the aqueous dispersion of the first precursor preferably includes the first precursor, a surfactant and water.
[0076] Among them, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as dodecyldimethylbenzylammonium bromide.
[0077] The ratio of the first precursor, the surfactant and the water is preferably (3-5) g: (0.3-0.5) mol: 300 mL, for example 4 g: 0.45 mol: 300 mL.
[0078] In S2 of the present invention, the type of the emulsifier may be an emulsifier having a hydrophile-lipophile balance (HLB) of 3-8, preferably an emulsifier having a hydrophile-lipophile balance (HLB) of 4-7, and more preferably one or more of propylene glycol fatty acid esters, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or glyceryl monostearate.
[0079] In S2 of the present invention, the type of the oil phase solvent in the oil phase solution containing the emulsifier can be conventional in the art, and is preferably an olefin having 12 to 28 carbon atoms, such as 1-octadecene.
[0080] In S2 of the present invention, the mass percentage of the emulsifier in the oil phase solution containing the emulsifier may be 0.3-0.8wt%, preferably 0.4-0.7wt%, for example 0.6wt%.
[0081] In S2 of the present invention, the mass ratio of the first precursor to the emulsifier may be 4:(0.9-2.4), for example, 4:1.8 or 4:1.2.
[0082] In S2 of the present invention, the method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 95-98°C.
[0083] In S2 of the present invention, the temperature of the heat treatment is preferably 450-600° C., such as 550° C. The time of the heat treatment is preferably 0.5-1.5 h, such as 1 h. The heat treatment is preferably performed in an air atmosphere.
[0084] In S2 of the present invention, the heat treatment preferably further includes a condensation step.
[0085] In S2 of the present invention, the structure of the second precursor may include a first precursor distributed in a cluster structure, the first precursor includes a tin-phosphorus composite material and a silicon dioxide layer coating the tin-phosphorus composite material, and the structure of the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance.
[0086] In S3 of the present invention, the temperature of the carbon coating may be 400-650° C., such as 450, 500 or 550° C. The time of the carbon coating may be 20-32 hours, such as 24 hours.
[0087] In S3 of the present invention, the type of carbon source for carbon coating can be conventional in the art, preferably phenolic resin and / or asphalt, such as phenolic resin fixed by surfactant.
[0088] Wherein, when the type of the carbon source is phenolic resin, the preparation method of carbon-coating the second precursor preferably comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the second precursor, polymerization reaction and carbon coating.
[0089] The molar ratio of the formaldehyde to the resorcinol may be (500-1000): (0.5-1.0), such as 750:1 or 1000:1. The catalyst may be a base, preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium hydroxide. The molar ratio of the resorcinol to the catalyst may be (0.5-1.0): (0.007-0.03), such as 0.8: 0.01 or 0.6: 0.01. The molar mass ratio of the resorcinol to the second precursor is preferably (0.5-1.0) mmol: (2-4) g, such as 0.8 mmol: 3.7 g, 0.8 mmol: 4.2 g or 0.6 mmol: 3.7 g. The temperature of the polymerization reaction may be 80-100° C., such as 85 or 90° C. The time of the polymerization reaction may be 8-10 h, such as 9 h. After the polymerization reaction and before the carbon coating, a drying step is preferably further included. Wherein, the drying operation may be conventional in the art, such as freeze drying, supercritical drying or vacuum drying. The freeze drying temperature may be -30 to -80°C, for example -60°C. The freeze drying time may be 3-7h, for example 4h. The supercritical drying temperature may be 10-40°C, for example 20 or 30°C. The supercritical drying time may be 1-3h, for example 1.5 or 2h. During the supercritical drying, the pressure of the system may be 10-15kPa, for example 10kPa. The vacuum drying temperature may be 80-100°C, for example 90°C. The vacuum drying time may be 10-20h, for example 18h.
[0090] Among them, when the type of the carbon source is a phenolic resin fixed with a surfactant, the preparation method of carbon-coating the second precursor preferably includes the following steps: an aqueous solution of a surfactant, resorcinol, formaldehyde, a catalyst and a second precursor, polymerization reaction and carbon coating.
[0091] The type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, for example dodecyldimethylbenzylammonium bromide.
[0092] In the aqueous solution of the surfactant, the molar ratio of the surfactant to the water is preferably (0.3-0.65):(8000-12000), for example 0.55:10000 or 0.45:10000.
[0093] The molar ratio of the surfactant to the resorcinol is preferably (0.3-0.65):(0.5-1.0), such as 0.45:0.6 or 0.45:0.8.
[0094] In S3 of the present invention, the carbon source is preferably further added with heteroatoms during the carbon coating.
[0095] Among them, when heteroatoms are added to the carbon source during the carbon coating, the preparation method of carbon coating the second precursor preferably includes the following steps: mixing the heteroatom source, resorcinol, formaldehyde, catalyst and the second precursor, polymerization reaction and carbon coating.
[0096] The type of the heteroatom may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen. When the type of the heteroatom is nitrogen, the type of the nitrogen source may be a nitrogen-containing substance, preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as p-nitroaniline.
[0097] The molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.0), for example 0.03:0.8 or 0.03:0.6.
[0098] In S3 of the present invention, the method for removing the silicon dioxide layer may be etching. The etching solution used for the etching is preferably a hydrofluoric acid solution. The mass percentage of hydrofluoric acid in the hydrofluoric acid solution is preferably 4-6wt%, such as 5wt%.
[0099] In S3 of the present invention, the structure of the third precursor may include a cluster structure; the cluster structure includes a plurality of tin-phosphorus-carbon composite particles, and second gaps are distributed between the tin-phosphorus-carbon composite particles;
[0100] Among them, a single tin-phosphorus-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, and a first gap is distributed between the shell layer and the inner core; wherein the inner core includes a tin-phosphorus composite material, and the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance; the shell layer includes a carbon layer.
[0101] In S3 of the present invention, preferably, the structure of the third precursor includes a cluster structure; the cluster structure includes a plurality of tin-phosphorus-carbon composite particles, and second gaps are distributed between the tin-phosphorus-carbon composite particles;
[0102] Among them, a single tin-phosphorus-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, and a first gap is distributed between the shell layer and the inner core; wherein the inner core includes a tin-phosphorus composite material, and the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance; the shell layer includes a carbon layer, and the carbon layer also includes heteroatoms.
[0103] In S4 of the present invention, the carbon source used for the graphene coating may be a conventional carbon source capable of forming graphene in the art, preferably humic acid.
[0104] Among them, when the carbon source is humic acid, the third precursor, humic acid and water are preferably mixed first during the graphene coating, and an ammonia solution is added dropwise under stirring to remove the solvent.
[0105] The amount of water used is not limited, so that the solid-liquid ratio in the mixed solution of the third precursor, humic acid and water is preferably 1:(10-20), for example 1:14.
[0106] The ammonia content in the aqueous ammonia solution is preferably 25%-30%, for example 28%. The amount of the aqueous ammonia solution used is not limited, as long as the humic acid powder is completely dissolved.
[0107] The method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 80-100°C, such as 90°C.
[0108] In S4 of the present invention, the mass ratio of the third precursor to the carbon source during graphene coating may be 100:(10-20), preferably 100:(11-18), for example 100:13 or 100:16.
[0109] In S4 of the present invention, the graphene coating is preferably performed by a first-stage sintering, cooling and a second-stage sintering, and the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering.
[0110] The temperature of the first sintering step is preferably 200-350°C, such as 260 or 300°C. The time of the first sintering step is preferably 6-15h, such as 12h. The first sintering step is preferably performed in a microwave oven. The power of the microwave oven can be 800-1100W, such as 1000W.
[0111] The end point of the cooling may be room temperature, generally 20-30°C.
[0112] Wherein, the temperature of the second stage sintering is preferably 400-600°C, such as 550 or 430°C. The time of the second stage sintering is preferably 20-30h, such as 26h. The rate of heating from room temperature to the temperature of the second stage sintering can be 1-10°C / min, such as 5°C / min. The second stage sintering is preferably carried out in a tubular furnace. The second stage sintering is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen.
[0113] In S4 of the present invention, the tin-phosphorus-carbon composite material may include a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-phosphorus-carbon composite particles, and second gaps are distributed between the tin-phosphorus-carbon composite particles;
[0114] Among them, a single tin-phosphorus-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, and a first gap is distributed between the shell layer and the inner core; wherein the inner core includes a tin-phosphorus composite material, and the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance; the shell layer includes a carbon layer.
[0115] In S4 of the present invention, preferably, the tin-phosphorus-carbon composite material comprises a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure comprises a plurality of tin-phosphorus-carbon composite particles, and second gaps are distributed between the tin-phosphorus-carbon composite particles;
[0116] Among them, a single tin-phosphorus-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, and a first gap is distributed between the shell layer and the inner core; wherein the inner core includes a tin-phosphorus composite material, and the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance; the shell layer includes a carbon layer, and the carbon layer also includes heteroatoms.
[0117] The invention provides a tin-phosphorus-carbon composite material, which is prepared by the preparation method of the tin-phosphorus-carbon composite material as mentioned above.
[0118] The present invention also provides a pole piece, which comprises the tin-phosphorus-carbon composite material as described above.
[0119] The present invention also provides an electrochemical device, which comprises the pole piece as described above.
[0120] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0121] The reagents and raw materials used in the present invention are commercially available.
[0122] The positive and progressive effects of the present invention are:
[0123] (1) The present invention produces a tin-phosphorus composite material, which includes a porous tin-containing material and red phosphorus particles deposited in the porous tin-containing material; the porous structure in the porous tin-containing material provides space for the volume expansion of the red phosphorus particles, and the tin material has a high electrical conductivity, which can make up for the defect of poor electrical conductivity of the phosphorus particles; in addition, the phosphorus particles have a good capacity performance, which can complement the lower capacity of the tin material, and the battery assembled from the tin-phosphorus composite material has a good capacity performance and cycle performance.
[0124] (2) The present invention produces a tin-phosphorus-carbon composite material, which includes a cluster structure and a graphene carbon layer. The cluster structure includes a plurality of tin-phosphorus-carbon composite particles. A single tin-phosphorus-carbon composite particle includes a phosphorus-tin composite material and a carbon layer. The phosphorus-tin composite material includes a porous tin-containing material and red phosphorus particles deposited in the porous tin-containing material. First, the porous structure in the porous tin-containing material provides space for the volume expansion of the red phosphorus particles, and the tin material has a high electrical conductivity, which can make up for the defect of poor electrical conductivity of the phosphorus particles. In addition, the capacity performance of the phosphorus particles is better, which can complement the lower capacity of the tin material. Secondly, in a single tin-phosphorus-carbon composite particle, the gap between the core and the shell provides another guarantee for the volume expansion of the phosphorus particles. Furthermore, gaps are distributed between a plurality of tin-phosphorus-carbon composite particles, which further alleviates the volume expansion of the phosphorus particles. Finally, the graphene coating layer has good electrical conductivity and mechanical properties, which provides another line of defense for the volume expansion of the phosphorus particles and can make the tin-phosphorus-carbon composite material have good electrochemical properties.
[0125] (3) The preparation method of the tin-phosphorus-carbon composite material of the present invention is simple, does not require the involvement of a large amount of chemical reagents, is highly practical, can be operated on a large scale, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0126] Figure 1 The figure is a flow chart of a method for preparing a tin-phosphorus-carbon composite material in an embodiment of the present invention. DETAILED DESCRIPTION
[0127] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0128] Example 1
[0129] S1. Preparation of tin-phosphorus composite material:
[0130] (1) Mix anhydrous tin chloride (80 mmol) and deionized water (135 mL) and stir for 40 min until the anhydrous tin chloride is completely dissolved. After sufficient stirring, add 2 mol / L sodium hydroxide solution (prepared using 67.5 mL deionized water) dropwise into the above aqueous solution of anhydrous tin chloride. Under a nitrogen atmosphere, continue the reaction at 60-80 ° C for 55 min, and maintain the pH value of the system at 5-12 (the molar ratio of stannous chloride to sodium hydroxide is 1:1.6875). Filter the obtained precipitate and rinse it repeatedly with water and ethanol. Then dry it under vacuum at 90 ° C overnight to obtain porous tin dioxide.
[0131] (2) Red phosphorus and the porous tin dioxide prepared in step S1 (1) are placed in a sealed stainless steel container (oxygen bomb) at a mass ratio of 6:3 (a total of 20 g), and then placed in a pyrolysis furnace filled with inert gas (the pressure of the system is 1 MPa), with a heating rate of 6°C / min and a temperature of 450°C for 3 hours. It is then cooled to 260°C at a cooling rate of 2°C / min for 22 hours, and then naturally cooled to room temperature, and washed and purified with carbon disulfide to remove unconverted white phosphorus to obtain a tin-phosphorus composite material. The structure of the tin-phosphorus composite material includes porous tin oxide and red phosphorus particles deposited in the porous tin oxide (the D50 of the red phosphorus particles is 50 μm).
[0132] S2. Preparation of the first precursor: (1) 7 mL of tetraethyl orthosilicate and 4 g of the tin-phosphorus composite material obtained in step S1 are sequentially added to 250 mL of a 28% ammonia solution, mixed and stirred for 55 min, filtered and cleaned, and pickled with 2 mol / L hydrochloric acid, filtered and cleaned again, and dried; then, heat treated at 350°C at a heating rate of 3°C / min for 24 h to fix the silicon dioxide layer, thereby obtaining the first precursor. The first precursor includes the tin-phosphorus composite material and the silicon dioxide layer coating the tin-phosphorus composite material.
[0133] Preparation of the second precursor: (2) 4 g of the first precursor prepared in step S2 (1) is uniformly dispersed in 300 mL of deionized water containing 0.45 mol of a surfactant (dodecyl dimethyl benzyl ammonium bromide) to form an aqueous dispersion, and mixed with 300 mL of a 1-octadecene solution containing 0.6 wt% of diethylene glycol monolaurate to form an oil-in-water emulsion. After evaporating the solvent at 95-98°C, the mixture is collected by centrifugation, and then heat-treated at 550°C for 1 h in an air atmosphere to remove organic matter, and then condensed to form a second precursor. The structure of the second precursor includes the first precursor distributed in a clustered structure.
[0134] S3, preparation of the third precursor: 0.45mmol surfactant (dodecyldimethylbenzyl ammonium bromide) and 10mol deionized water were mixed and ultrasonically dispersed for 55min to form spherical micelles. Then, a mixture of p-nitroaniline (0.03mmol), resorcinol (0.8mmol), formaldehyde (0.6mol) and sodium hydroxide (0.01mmol) was added and stirred continuously. Subsequently, 3.7g of the second precursor prepared in step S2 (2) was added. Then, polymerization was carried out at 85℃ for 9h. After vacuum drying at 90℃ for 18h, carbon coating was carried out at 450℃ for 24h under nitrogen atmosphere. Finally, the silica layer was removed with 5wt% HF solution to obtain the third precursor. The structure of the third precursor includes a cluster structure; the cluster structure includes a plurality of tin-phosphorus-carbon composite particles, and second voids are distributed between the tin-phosphorus-carbon composite particles; a single tin-phosphorus-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core, and first voids are distributed between the shell layer and the inner core; the inner core includes a tin-phosphorus composite material, and the tin-phosphorus composite material includes porous tin oxide and red phosphorus particles deposited in the porous tin oxide; the shell layer includes a carbon layer, and the carbon layer also includes nitrogen doping.
[0135] S4. The third precursor prepared in step S3 is mixed with humic acid (model 53680-10G, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) in a mass ratio of 100:13, and added into deionized water for uniform mixing, the solid-liquid ratio is controlled at 1:14, and then a 28wt% ammonia solution is added dropwise under stirring until the humic acid powder is completely dissolved, and then heated to 90°C and the solvent is evaporated to make the humic acid evenly coated on the surface of the third precursor, and sintered at 300°C for 12h in a microwave oven (microwave power of 1000W), cooled to room temperature, taken out, and then placed in a tubular furnace under an inert atmosphere, heated from room temperature to 550°C at a rate of 5°C / min, and sintered for 26h in a second stage, so that the humic acid is thermally decomposed to synthesize graphene in situ, and a tin-phosphorus-carbon composite material is obtained. The tin-phosphorus-carbon composite material includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-phosphorus-carbon composite particles, and second gaps are distributed between the tin-phosphorus-carbon composite particles; wherein a single tin-phosphorus-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer coating the inner core, and first gaps are distributed between the shell layer and the inner core; wherein the inner core includes a tin-phosphorus composite material, and the tin-phosphorus composite material includes porous tin oxide and red phosphorus particles deposited in the porous tin oxide; and the shell layer includes a carbon layer, and the carbon layer also includes nitrogen doping.
[0136] Example 2
[0137] The difference from Example 1 is that the inorganic tin source in step S1 (1) is stannous chloride.
[0138] Example 3
[0139] The difference from Example 1 is that in step S1 (2), the mass ratio of red phosphorus to porous tin dioxide is 8:3.
[0140] Example 4
[0141] The difference from Example 1 is that the pyrolysis temperature in step S1 (2) is 400°C.
[0142] Example 5
[0143] The difference from Example 1 is that the cooling time in step S1 (2) is 26 hours.
[0144] Example 6
[0145] The difference from Example 1 is that the silicon source in step S2 (1) is methyl orthosilicate.
[0146] Example 7
[0147] The difference from Example 1 is that 3.5 g of tin-phosphorus composite material is added in step S2 (1).
[0148] Example 8
[0149] The difference from Example 1 is that in step S2 (2), a 0.4 wt % diethylene glycol monolaurate 1-octadecene solution is used.
[0150] Example 9
[0151] The difference from Example 1 is that the emulsifier in step S2 (2) is glyceryl monostearate.
[0152] Example 10
[0153] The difference from Example 1 is that 4.2 g of the second precursor is used in step S3.
[0154] Embodiment 11
[0155] The difference from Example 1 is that 0.6 mmol of diphenol is added in step S3.
[0156] Example 12
[0157] The difference from Example 1 is that the carbon coating temperature in step S3 is 400°C.
[0158] Embodiment 13
[0159] The difference from Example 1 is that in step S4, the mass ratio of the third precursor to humic acid is 100:16.
[0160] Embodiment 14
[0161] The difference from Example 1 is that the sintering temperature in step S4 is 260°C.
[0162] Embodiment 15
[0163] The difference from Example 1 is that the second-stage sintering temperature in step S4 is 430°C.
[0164] Comparative Example 1
[0165] The difference from Example 1 is that the negative electrode material is pure tin powder.
[0166] Comparative Example 2
[0167] The difference from Example 1 is that the negative electrode material is pure phosphorus powder.
[0168] Example 16
[0169] The difference from Example 1 is that only a tin-phosphorus composite material is used, that is, only steps S1 (1) and (2) are included.
[0170] Comparative Example 3
[0171] The difference from Embodiment 1 is that steps S2 and S3 are omitted.
[0172] Comparative Example 4
[0173] S1. Preparation of tin-phosphorus composite material:
[0174] (1) Mix anhydrous tin chloride (80 mmol) and deionized water (135 mL) and stir for 40 min until the anhydrous tin chloride is completely dissolved. After sufficient stirring, add 2 mol / L sodium hydroxide solution (prepared using 67.5 mL deionized water) dropwise into the above aqueous solution of anhydrous tin chloride. Under a nitrogen atmosphere, continue the reaction at 60-80 ° C for 55 min, and maintain the pH value of the system at 5-12. Filter the obtained precipitate and rinse it repeatedly with water and ethanol. Then dry it under vacuum at 90 ° C overnight to obtain porous tin dioxide.
[0175] (2) Red phosphorus and the porous tin dioxide prepared in step S1 (1) are placed in a sealed stainless steel container (oxygen bomb) at a mass ratio of 6:3 (a total of 20 g), and then placed in a pyrolysis furnace filled with inert gas (the pressure of the system is 1 MPa), with a heating rate of 6°C / min and a temperature of 450°C for 3 hours. It is then cooled to 260°C at a cooling rate of 2°C / min for 22 hours, and then naturally cooled to room temperature, and washed and purified with carbon disulfide to remove unconverted red phosphorus to obtain a tin-phosphorus composite material. The structure of the tin-phosphorus composite material includes porous tin oxide and red phosphorus particles deposited in the porous tin oxide.
[0176] S2, preparation of the first precursor: 7mL of tetraethyl orthosilicate and 4g of the tin-phosphorus composite material obtained in step S1 are added to 250mL of ammonia solution with a mass concentration of 28%, mixed and stirred for 55min, filtered and cleaned, and pickled with 2mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 350°C, the heating rate is 3°C / min, and the silicon dioxide layer is fixed for 24h to obtain the first precursor. The first precursor includes the tin-phosphorus composite material and the silicon dioxide layer coating the tin-phosphorus composite material.
[0177] S3, preparation of the second precursor: 0.45mmol surfactant (dodecyldimethylbenzyl ammonium bromide) and 10mol deionized water were mixed and ultrasonically dispersed for 55min to form spherical micelles. Then a mixture of p-nitroaniline (0.03mmol), resorcinol (0.8mmol), formaldehyde (0.6mol) and sodium hydroxide (0.01mmol) was added and stirred continuously. Subsequently, 3.7g of the first precursor prepared in step S2 was added. Then polymerized at 85℃ for 9h. After vacuum drying at 90℃ for 18h, carbon coated at 450℃ for 24h under nitrogen atmosphere. Finally, the silica layer was removed with 5wt% HF solution to obtain the second precursor. The structure of the second precursor includes tin-phosphorus-carbon composite particles; the tin-phosphorus-carbon composite particles have a core-shell structure, which includes an inner core and a shell layer covering the inner core, and a first gap is distributed between the shell layer and the inner core; wherein the inner core includes a tin-phosphorus composite material, a tin-phosphorus composite material porous tin oxide and red phosphorus particles deposited in the porous tin oxide; the shell layer includes a carbon layer, and the carbon layer also includes nitrogen doping.
[0178] S4. The second precursor prepared in step S3 is mixed with humic acid in a mass ratio of 100:13, and the mixture is added into deionized water and mixed evenly, with the solid-liquid ratio controlled at 1:14. Then, an aqueous ammonia solution with a concentration of 28wt% is added dropwise under stirring until the humic acid powder is completely dissolved. The mixture is heated to 90°C and the solvent is evaporated to make the humic acid evenly coat the surface of the second precursor. The mixture is sintered at 300°C for 12h in a microwave oven (with a microwave power of 1000W), cooled to room temperature, taken out, and then placed in a tubular furnace under an inert atmosphere and heated from room temperature to 550°C at a rate of 5°C / min for 26h in a second stage to thermally decompose the humic acid and synthesize graphene in situ to obtain a tin-phosphorus-carbon composite material. The tin-phosphorus-carbon composite material includes tin-phosphorus-carbon composite particles and a graphene layer coated on the surface of the tin-phosphorus-carbon composite particles; the tin-phosphorus-carbon composite particles have a core-shell structure, which includes an inner core and a shell layer coating the inner core, and a first gap is distributed between the shell layer and the inner core; wherein the inner core includes the tin-phosphorus composite material, the tin-phosphorus composite material includes porous tin oxide and red phosphorus particles deposited in the porous tin oxide; the shell layer includes a carbon layer, and the carbon layer also includes nitrogen doping.
[0179] Effect Example 1
[0180] The inductively coupled plasma (ICP) method is used to test the element content (tin, carbon, oxygen and nitrogen content) in the tin-carbon composite material prepared by the present invention. The test method is as follows: (1) Pre-treatment by microwave digestion method, 0.5g of the tin-carbon composite material prepared in the embodiment or the comparative example is placed in a digestion tank, 3mL of concentrated nitric acid and 9mL of concentrated sulfuric acid are added in sequence with a liquid adder, and the mixture is shaken well; and the mixture is kept at a constant temperature of 160°C for 3min, 180°C for 3min, 200°C for 10min, and 220°C for 10min, and then cooled to room temperature, filtered with quantitative filter paper, and the filtrate is placed in a 50mL volumetric flask as the test solution; (2) The above test solution is tested in the PerkinElmer ICP spectrometer Avio™ 200 device; the test condition is an air pressure of 2.5MPa.
[0181] The D50 of the tin-phosphorus-carbon composite materials prepared in the examples and comparative examples was tested using a Malvern particle size tester.
[0182] The conductivity was measured at room temperature using an Orion Star™ A212 conductivity benchtop meter.
[0183] The charge transfer resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 )get.
[0184] The above physical and chemical results are shown in Table 1 below.
[0185] Table 1
[0186]
[0187] Note: The content of each element indicates the percentage of the mass of each element to the mass of the tin-phosphorus-carbon composite material.
[0188] Effect Example 2
[0189] The preparation method of the button cell used for testing the electrochemical performance is as follows: the tin-phosphorus-carbon composite material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil with a compaction density of 1.60 g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte using 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is PE / PP / PE composite film, and assembled into a button battery.
[0190] The above button cell was subjected to various electrical performance tests on a blue battery tester, the test condition was 25°C, and the charging voltage limit was 0.005-2V.
[0191] (1) First discharge specific capacity and first coulombic efficiency
[0192] The charge and discharge were carried out at a rate of 0.1C, and the first discharge specific capacity and the first coulombic efficiency were tested. The test results are shown in Table 2.
[0193] (2) Cycle performance
[0194] The charge and discharge cycles were performed 300 times at a rate of 0.1C, and the 300th discharge specific capacity was recorded as the 300-cycle retention capacity. The test results are shown in Table 2.
[0195] Table 2
[0196]
[0197] (3) Rate performance
[0198] The test conditions for rate performance are: rate charge and discharge at a current density of 0.1C-3C, and the charging voltage is limited to 0.005-2V. The rate performance is tested at a current density of 0.1C. The results are shown in Table 3.
[0199] Table 3
[0200]
[0201] It can be seen from Table 2 and Table 3 that, compared with Comparative Examples 1-2, the tin-phosphorus composite material prepared in Example 16 has better first coulombic efficiency, cycle performance and rate performance, and has a lower pole piece expansion rate.
[0202] Compared with comparative examples 1-4, the tin-phosphorus-carbon composite material obtained in examples 1-15 includes a cluster structure and a graphene layer, and the cluster structure includes a plurality of tin-phosphorus-carbon composite particles; a single tin-phosphorus-carbon composite particle includes a tin-phosphorus composite material and a carbon layer; the tin-phosphorus composite material includes a porous tin oxide and red phosphorus particles deposited in the porous tin oxide; first, the porous structure in the porous tin oxide provides space for the volume expansion of the red phosphorus particles, and the tin material has a high electrical conductivity, which can make up for the defect of poor electrical conductivity of the phosphorus particles; in addition, the capacity performance of the phosphorus particles is better, which can complement the lower capacity of the tin material; secondly, in a single tin-phosphorus-carbon composite particle, the gap between the core and the shell provides another guarantee for the volume expansion of the phosphorus particles; further, gaps are distributed between the tin-phosphorus-carbon composite particles distributed in a cluster structure, which further alleviates the volume expansion of the phosphorus particles; finally, the graphene coating has good electrical conductivity and mechanical properties, provides another line of defense for the volume expansion of the phosphorus particles, and can make the tin-phosphorus-carbon composite material have good electrochemical properties. Therefore, the tin-phosphorus-carbon composite materials prepared in Examples 1-15 have better first coulombic efficiency, cycle performance and rate performance than the tin-phosphorus-carbon composite materials prepared in Comparative Examples 1-4.
Claims
1. A tin-phosphorus composite material, characterized in that: The invention comprises a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance.
2. The tin-phosphorus composite material according to claim 1, characterized in that The tin-phosphorus composite material satisfies one or more of the following conditions AC: A. The porous tin-containing material includes one or more of porous tin oxide, porous stannous oxide and porous tin, such as porous tin oxide; B. The D50 of the red phosphorus particles is 20-100 μm, preferably 40-80 μm, for example 50, 60 or 70 μm; C. In the tin-phosphorus composite material, the mass ratio of phosphorus to tin is (1-2):1, preferably (1.2-1.8):1, for example, 1.65:1, 1.59:1, 1.57:1, 1.56:1, 1.55:1, 1.52:1, 1.51:1, 1.50:1, 1.49:1, 1.46:1 or 1.44:
1.
3. A method for preparing a tin-phosphorus composite material, characterized in that: The method comprises the following steps: heat treating and cooling a mixture of red phosphorus and porous tin-containing material to obtain a phosphorus-tin composite material; the heat treatment temperature is 400-500° C.; Preferably, the mass ratio of the red phosphorus to the porous tin-containing material is (6-8):(2-4), preferably (6-8):(2.5-3.5), for example 6:3 or 8:3; Preferably, the porous tin-containing material comprises one or more of porous tin oxide, porous stannous oxide and porous tin, such as porous tin oxide; The porous tin oxide is preferably prepared by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12; The type of the inorganic tin source is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride or stannous chloride; the molar ratio of the inorganic tin source to the base is preferably 1:(1.0-2.0), more preferably 1:(1.5-1.8), such as 1:1.6875; the reaction temperature is preferably 50-90°C, such as 60-80°C; the reaction time is preferably 40-60min, such as 50 or 55min; Preferably, the temperature of the heat treatment is 420-480°C, for example 450°C; Preferably, the rate of heating from room temperature to the temperature of the heat treatment is 5-10°C / min, such as 6, 7, 8 or 9°C / min; Preferably, the heat treatment time is 2-4 hours, for example 3 hours; Preferably, the initial pressure of the system during the heat treatment is 0.5-1.5 MPa, for example 1 MPa; Preferably, the cooling end point temperature is 260-300°C, such as 260, 270, 280 or 290°C; Preferably, the cooling rate from the heat treatment temperature to the cooling end point temperature is 1-3°C / min, for example 2°C / min; Preferably, after cooling to the terminal temperature, the cooling time is continued for 16-28 hours, such as 22 or 26 hours.
4. A tin-phosphorus composite material, characterized in that: The tin-phosphorus composite material is prepared by the preparation method of the tin-phosphorus composite material as claimed in claim 3.
5. A tin-phosphorus-carbon composite material, characterized in that: It includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-phosphorus-carbon composite particles, and second gaps are distributed between the tin-phosphorus-carbon composite particles; The single tin-phosphorus-carbon composite particle has a core-shell structure, which includes a core and a shell layer covering the core, and a first gap is distributed between the shell layer and the core; wherein the core includes a tin-phosphorus composite material, the tin-phosphorus composite material includes a porous tin-containing substance and red phosphorus particles deposited in the porous tin-containing substance; the shell layer includes a carbon layer; The D50 of the tin-phosphorus-carbon composite material is preferably 300-460 nm, more preferably 330-430 nm, such as 410, 400, 380, 370, 360 or 350 nm; The phosphorus content of the tin-phosphorus-carbon composite material is preferably 32%-45%, more preferably 35%-42%, such as 39.9%, 39.4%, 39.2%, 38.9%, 38.7%, 38.5%, 38.4%, 38.1%, 37.8%, 37.6% or 37.5%; The tin content of the tin-phosphorus-carbon composite material is preferably 19%-31%, more preferably 22%-28%, such as 26.3%, 26.1%, 25.9%, 25.7%, 25.6%, 25.3%, 25.1%, 24.9%, 24.8% or 24.2%; The content of each element above indicates the percentage of the mass of each element to the mass of the tin-phosphorus-carbon composite material; In the single tin-phosphorus-carbon composite material, the carbon layer preferably further includes heteroatoms; Wherein, the type of the heteroatom is preferably one or more of nitrogen, phosphorus, sulfur and boron, such as nitrogen; Among them, the content of heteroatoms is preferably 0.1-0.65%, more preferably 0.2%-0.55%, for example 0.87%, 0.83%, 0.82%, 0.77%, 0.76%, 0.75%, 0.74%, 0.72%, 0.71%, 0.69%, 0.68% or 0.59%; the content of heteroatoms represents the percentage of the mass of heteroatoms to the mass of the tin-phosphorus-carbon composite material.
6. A method for preparing a tin-phosphorus-carbon composite material, characterized in that: It includes the following steps: S1, heat-treating and cooling a mixture including red phosphorus and a porous tin-containing substance to obtain a tin-phosphorus composite material; the heat-treating temperature is 400-500° C.; S2, coating the tin-phosphorus composite material with silicon dioxide to form a silicon dioxide layer to obtain a first precursor; mixing the aqueous dispersion of the first precursor and an oil phase solution containing an emulsifier, removing the solvent and performing heat treatment to obtain a second precursor; S3, carbon-coating the second precursor, removing the silicon dioxide layer, and obtaining a third precursor; S4, coating the third precursor with graphene to obtain a tin-phosphorus-carbon composite material.
7. The method for preparing the tin-phosphorus-carbon composite material according to claim 6, characterized in that: The preparation method of the tin-phosphorus-carbon composite material meets one or more of the following conditions AU: In A and S1, the mass ratio of the red phosphorus to the porous tin-containing material is (6-8):(2-4), preferably (6-8):(2.5-3.5), for example 6:3 or 8:3; In B and S1, the porous tin-containing material includes one or more of porous tin oxide, porous stannous oxide and porous tin, such as porous tin oxide; C. In S1, the heat treatment temperature is 420-480°C, for example 450°C; D. In S1, the rate of heating from room temperature to the temperature of the heat treatment is 5-10°C / min, such as 6, 7, 8 or 9°C / min; In E and S1, the heat treatment time is 2-4 hours, for example, 3 hours; In F and S1, the initial pressure of the system during the heat treatment is 0.5-1.5 MPa, for example, 1 MPa; In G and S1, the cooling end temperature is 260-300°C, for example, 260, 270, 280 or 290°C; In H and S1, the cooling rate from the heat treatment temperature to the cooling end temperature is 1-3°C / min, for example, 2°C / min; In I and S1, after cooling to the end temperature, the cooling time is continued for 16-28 hours, for example, 22 or 26 hours; In J and S2, the method for preparing the tin-phosphorus composite material by coating it with silicon dioxide comprises the following steps: mixing the tin-phosphorus composite material, a silicon source and an ammonia solution, acid washing, and heat treating; Wherein, the type of the silicon source is preferably silicate or silicate; the silicate is preferably ethyl orthosilicate and / or methyl orthosilicate; the silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate; Wherein, the mass volume ratio of the tin-phosphorus composite material and the silicon source is preferably (2-5) g: (3-10) mL, for example, 4 g: 7 mL or 3.5 g: 7 mL; The heat treatment temperature is preferably 300-400°C, such as 350°C; the heat treatment time is preferably 15-30h, such as 24h; the rate of heating from room temperature to the heat treatment temperature is preferably 1-10°C / min, such as 3°C / min; In K and S2, the aqueous dispersion of the first precursor comprises the first precursor, a surfactant and water; Wherein, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as dodecyldimethylbenzylammonium bromide; Wherein, the ratio of the first precursor, the surfactant and the water is preferably (3-5) g: (0.3-0.5) mol: 300 mL, for example 4 g: 0.45 mol: 300 mL; In L and S2, the type of the emulsifier is an emulsifier with a hydrophile-lipophile balance value of 3-8, preferably an emulsifier with a hydrophile-lipophile balance value of 4-7, and more preferably one or more of propylene glycol fatty acid ester, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or glyceryl monostearate; In M and S2, the oil phase solvent in the oil phase solution containing the emulsifier is an olefin having 12 to 28 carbon atoms, such as 1-octadecene; In N and S2, the mass ratio of the first precursor to the emulsifier is 4:(0.9-2.4), for example, 4:1.8 or 4:1.2; In O and S2, the heat treatment temperature is 450-600°C, for example, 550°C; the heat treatment time is preferably 0.5-1.5h, for example, 1h; In P and S3, the carbon coating temperature is 400-650°C, such as 450, 500 or 550°C; the carbon coating time is preferably 20-32h, such as 24h; In Q and S3, the carbon source during carbon coating is phenolic resin and / or asphalt, such as phenolic resin fixed by surfactant; Wherein, when the type of the carbon source is phenolic resin, the preparation method of carbon-coating the second precursor preferably comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the second precursor, polymerizing and carbon-coating; The molar ratio of the formaldehyde to the resorcinol is preferably (500-1000): (0.5-1.0), such as 750:1 or 1000:1; the catalyst is preferably a base, more preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium hydroxide; the molar ratio of the resorcinol to the catalyst is preferably (0.5-1.0): (0.007-0.03), such as 0.8: 0.01 or 0.6: 0.01; the molar mass ratio of the resorcinol to the second precursor is preferably (0.5-1.0) mmol: (2-4) g, such as 0.8 mmol: 3.7 g, 0.8 mmol: 4.2 g or 0.6 mmol: 3.7 g; the temperature of the polymerization reaction is preferably 80-100°C, such as 85 or 90°C; the time of the polymerization reaction is preferably 8-10h, such as 9h; Wherein, when the type of the carbon source is a phenolic resin fixed by a surfactant, the preparation method of carbon-coating the second precursor preferably comprises the following steps: polymerizing and carbon-coating an aqueous solution of a surfactant, resorcinol, formaldehyde, a catalyst and a second precursor; The type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as dodecyldimethylbenzylammonium bromide; The molar ratio of the surfactant to the resorcinol is preferably (0.3-0.65):(0.5-1.0), such as 0.45:0.6 or 0.45:0.8; In R and S3, the carbon source is also added with heteroatoms during carbon coating; Wherein, when a heteroatom is added to the carbon source during the carbon coating, the preparation method of carbon coating the second precursor preferably comprises the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the second precursor, polymerizing and carbon coating; The type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; when the type of the heteroatom is nitrogen, the type of the nitrogen source is preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as p-nitroaniline; The molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.0), such as 0.03:0.8 or 0.03:0.6; In S and S4, the carbon source used in the graphene coating is humic acid; In T and S4, the mass ratio of the third precursor to the carbon source during graphene coating is 100:(10-20), preferably 100:(11-18), for example 100:13 or 100:16; In U and S4, the graphene coating is subjected to a first-stage sintering, cooling and a second-stage sintering, and the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering; The temperature of the first sintering step is preferably 200-350°C, such as 260 or 300°C; the time of the first sintering step is preferably 6-15h, such as 12h; the first sintering step is preferably performed in a microwave oven; the power of the microwave oven is preferably 800-1100W, such as 1000W; Among them, the temperature of the second stage sintering is preferably 400-600°C, such as 550 or 430°C; the time of the second stage sintering is preferably 20-30h, such as 26h; the rate of heating from room temperature to the temperature of the second stage sintering is preferably 1-10°C / min, such as 5°C / min.
8. A tin-phosphorus-carbon composite material, characterized in that: The tin-phosphorus-carbon composite material is prepared by the preparation method of the tin-phosphorus-carbon composite material as claimed in claim 6 or 7.
9. A pole piece, characterized in that: It comprises the tin-phosphorus-carbon composite material as described in any one of claims 5-7.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of phosphorus-carbon composite negative electrode material, negative electrode and lithium ion battery
CN116759556A